Framework to assess driver’s visibility at road junction / Kushairi Rashid ... [et al.] - Rashid, Kushairi; Azwan Azman, Muhammad Azrul; Mohd Arip, Mohd Sabri; Mohamad Rodzi, Nurzarith Shafiqah (Universiti Teknologi MARA, Perak, 2020)
Modern lifestyles do influence Malaysian occupants to work long hours in a day in order to cope with large workloads and to meet a deadline. Majority of the occupants are overstressed, faced with negative emotions that lead to an unhealthy lifestyle. Studies show that nature is able to enhance human well-being by reconnecting human with natural elements in a built environment, which is known as biophilic design. Therefore, this study aims to create a biophilic design guideline to enhance occupants' well-being in heritage adaptive reuse indoor co-working space. This study is conducted in the Heritage World Site (WHS) in George Town, Penang. Mixed method research design was used to collect data from the site. Both qualitative and quantitative data were analysed using the triangulation method to validate the overall data and research by cross verifying the information from multiple methods to gather the data. The results proved that the existing biophilic design patterns do enhance co-workers' emotional well-being significantly and it can be used as design guideline. In addition, this study also investigated different ways of biophilic design patterns application which can affect the quality of biophilic experiences.